Epidemiology of fractures: The role of kick injuries in equine fractures. (28th February 2018) - Donati, B.; Fürst, A. E.; Hässig, M.; Jackson, M. A.
Summary: Background: Fractures occur commonly in equids and often are associated with complications and a poor outcome. There are no reports on the epidemiology of fractures in a heterogeneous equine population. Objectives: To study the epidemiology of fractures in a heterogeneous equine population, focusing on differences between fractures resulting from a kick and fractures, resulting from other causes and investigating predictors for recovery. Study design: Retrospective case series. Methods: Data of all equids presented to the Equine Department, Vetsuisse Faculty, University of Zurich between 1990 and 2014 and diagnosed with a fracture were reviewed and those with a known cause were included in this study. Mann–Whitney and chi‐squared tests were used to compare recovery rates of fractures resulting from a kick and fractures resulting from other causes, and a logistic regression was carried out for multivariate analysis of the most important factors affecting recovery. Results: Here, 1144 cases fulfilled the inclusion criteria. Of all fractures (with a known cause), 43.6% were the result of a kick from another equid. Kicks often produced open fractures (44.7%) that involved bones of the limbs (85.6%). Overall recovery was 70.1%. Logistic regression showed that high‐grade lameness accompanying the fracture and severe comminution negatively affected recovery. Main limitations: The equids in this study were drawn from a referred population, which likely precluded the inclusion of both minor fractures and catastrophic fractures that necessitated immediate euthanasia. Moreover, many cases were excluded because the cause of the fracture could not be determined from the patient record. Conclusions: Kicks are the most common cause of fractures in a heterogeneous equine population and measures to reduce the incidence of kicks are necessary in group‐housing systems.